Improving physical activity maintenance following an exercise program for cancer survivors: a pragmatic hybrid randomized controlled trial - McGinnis, Emma L., author; Leach, Heather, advisor; Fruhauf, Christine, committee member; Rogers, Laura, committee member; Jankowski, Catherine, committee member (Colorado State University. Libraries, 2020)
Purpose: Supervised exercise programs can help cancer survivors increase physical activity (PA), but maintaining PA following program completion is challenging. Randomized controlled trials have shown that adding behavior change counseling to supervised exercise can improve PA maintenance in cancer survivors, however, translating this work to real-world settings remains a challenge. This study examined (1) the feasibility and acceptability of implementing six, evidence-based PA behavior change counseling (PABCC) sessions into BfitBwell, an existing exercise program for cancer survivors, and (2) the effects of PABCC on post-program self-efficacy and outcome expectations, and on PA, 3-months following program completion. Methods: Cancer survivors enrolled in BfitBwell were randomized to receive (1) the current BfitBwell program, or (2) BfitBwell plus six PABCC sessions. Feasibility was assessed by participant representativeness, process fidelity, time and cost to adapt and deliver the PABCC sessions, and a focus group with BfitBwell staff. Acceptability was based on reasons for declining participation, adherence, and participant satisfaction. Barriers self-efficacy, exercise self-efficacy, outcome expectations, and PA were assessed via validated questionnaires at baseline, post-program, and 3-month follow-up (PA only). Quantitative feasibility and acceptability data were summarized using descriptive statistics and qualitative data were analyzed using thematic content analysis. Paired sample t-tests examined within group changes in self-efficacy and outcome expectations. Change in minutes of moderate to vigorous PA (MVPA) was calculated by subtracting MVPA at post-program from 3-month follow up, and the percent of participants meeting PA guidelines was calculated. Results: Out of (N=33) who enrolled, N=13 completed the post-program assessment, and N=9 completed the 3-month follow-up exercise questionnaire. Based on the staff focus group and study evaluation questionnaire, PABCC was well accepted and the idea of incorporating a behavior change component into BfitBwell was well supported by program staff. However, due to low enrollment rates (35%), reasons for declining participation such as "unable to make class time", and the staff time associated with delivering PABCC sessions, implementation of the sessions in their current form may not be feasible. There was no significant change in self-efficacy or outcome expectation measures from baseline to post-program. Minutes of MVPA tended to decline from post-intervention to three-month follow-up in both BfitBwell + PABCC (-81.7 ± 240.6) and control (-45.0 ± 63.7), however PA response was highly variable. Additional research to explore alternative PABCC delivery strategies such as virtual delivery modalities or a condensed PABCC format in the context of existing exercise programs is needed. Further, a study with a larger sample size is needed to confirm the effectiveness of adding PABCC to BfitBwell on PA maintenance.
Keywords: oncology; social cognitive theory; physical activity; behavioral intervention